WAQF SYSTEM DURING SOUTHEAST ASIA'S DECOLONIZATION PERIOD - Widiyanti, Dwi Retno; Pudjihardjo, Muhammad; Ekawaty, Marlina; Manzilati, Asfi (I-iECONS e-proceedings, 2023)
The purpose of this research is to contrast the Waqf systems in Southeast Asian nations with Muslim majorities. This study employs a qualitative literature review methodology. The most frequently cited works listed in trustworthy journals indexed by scopus were used for this study. The analysis of the waqf system in this paper takes place in the years following these nations' independence from colonial rule. The Waqf legal structure and the governing bodies that oversee it are the subject of the study. We selected a number of Southeast Asian nations, including Indonesia, Malaysia, Brunei Darussalam, and Singapore, as our sample of Muslim-majority nations. According to the data, the majority of waqf institutions in Southeast Asia are legitimate.